TAHLIL AL MA'ANY FI SYI'RI ROBI'ATI AL 'ADAWIYATI HAQIQATUL HUBBI : AL NAZHRATU AL SIMIYA'IYYATI AL RIFATIRY - Yolli Andriani (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
This study aims to describe (1) heuristic reading (2) hermeneutic reading (3) matrix, model, and (4) hypogram in the poem “Hakikat Cinta” by Rabi'ah Al-Adawiyah. This research is a library research because the primary data and secondary data are in the form of books or related documents. This study uses a qualitative descriptive technique through the semiotic approach of Michael Riffaterre. The results of the study are as follows. (1) The heuristic recitation of each sentence shows that this poem tells the story of Rabi'ah's love for his Lord, in this case he gave his whole life and death to Allah. (2) The Hermeneutic reading tells about the rabi'ah immense love for Allah, this is expressed in every verse that she expresses through her poetry. (3) The matrix in this poem is the praises conveyed by the Rabi'ah to the creator. (4) The hypogram in this poem is an intertextual hypogram, which is an explanation related to the poetry written by Rabi'ah which is closely related to the verses of the Qur'an an. After using the semiotic theory of the riffaterre, it can be concluded that according to Rabi'ah the only purpose of life that is very natural to be loved is Allah. The word love which is repeated every time by the rabi'ah implies the integrated meaning of all love only to Allah, because all forms of love and feelings grow because of the beauty and perfection of Allah